Ojciec Maksymilian Maria Kolbe – wyznawca czy męczennik? Teologiczno-kanoniczna kwalifikacja świadectwa o. M. M. Kolbego - Piotr Rossa (Wrocławski Przegląd Teologiczny)
This text shows the transformations which have taken place in the theological and canonical understanding of Christian witness on the occasion of the beatification and canonization process of Father Maximilian Maria Kolbe. These transformations concerned the understanding of who a Christian witness is in light of his life and his moment of death as well as – in the case of a martyr – the general makeup of the individual who acts as a persecutor. The beatification and canonization process of Father Kolbe have led to the discovery of how refined the twentieth century totalitarian systems’ persecution of Christians has become. This, in turn, has led to new situations, where particular cases of sanctity discussed in the canonical process have gone beyond already existing canonical norms.